MORFOLOGI DAN PERILAKU HAMA Crocidolomia pavonana PADA TANAMAN KUBIS - Frangky J. Paat; Jantje Pelealu (COCOS, 2020)
ABSTRACT This study aims to determine the morphology and behavior of Crocidolomia pavonana pests. The research was conducted at the Laboratory of Entomology and Plant Pests, Faculty of Agriculture, Sam Ratulangi University. This research used descriptive method and analyzed using excel and SPSS 19 software. Observations included size, shape, larva color, behavior, development stage of Crocidolomia pavonana. The measurement results of the larval instar of C. pavonana, first instar is 1,84-2,51 mm, second instar is 5,1-6,82 mm, the size of the third instar larva is 11,97-15,85 mm, and the size of the fourth instar larvae is 14,25-18,7 mm. Observation period of the larval instar of C. pavonana, first instar was 3-6 days, second instar period was 3-6 days, third instar period was 2-5 days, and fourth instar period was 3-8 days. The size of the egg group is 3-5 mm. Female body size is longer than male imago. The average female body size is ± 9-11,6 cm. The average male body size was 6,7-9,2 mm. The time period for hatching groups of eggs is 3-4,5 days. The results of the morphological study of Crocidolomia pavonana pest showed that the adult characteristics of the head color are orange, body color is cream to slightly yellow, wing color is brown with black spots, laying eggs under the leaves. Eggs are placed in groups and arranged, placed under the leaves in a group of eggs, greenish yellow and shiny, when they hatch, they are older and slightly reddish, hatch 4-5 days after laying. The larvae have four instars. When the first instar is still in groups and eats the leaves where the larvae hatch so that it forms like a window, spreads after entering the second instar, the green colored caterpillar on the back has a light green line, on the right and left sides the color is older, and there are chitine hairs, there are Also the caterpillars which are green with three rows of lighter color and side lines are green and yellow and the hair is green, the kettles forming pupae will drop in the ground under the cabbage plant and there are also pupae on the leaves. The first instar larvae are light green, the head is black and the body surface is covered with fine hairs. This larva is still weak and is mostly silent by covering its body with fine white threads that come out of its mouth. Second instar larvae when molting, pale green skin, reddish brown head. When molting the skin it is sometimes difficult to find skin marks, because the skin marks are eaten by the larvae. Usually all that is left is the hard part of the head. On the side of the larva's body there is a green ribbon. These second instar larvae have been actively moving to eat the leaves until they have holes. After reaching the third instar, the larvae disperse and begin to attack deeper leaves and often enter the shoots of the plant and destroy the growing point. Larvae usually eat together in a plant and eat the lower leaves without eating the upper membrane so that the leaves become transparent. The larva's body accumulates light green larval excrement. Fourth instar larvae are light green, the head and legs are brownish and the longitudinal green stripes on the body are more pronounced. In the intermediate stage from the larvae to the prepupa period, it is greenish yellow with a blackish head. On the back and side of the larvae there are longitudinal brown lines. Larvae are puppies in the soil and reddish in color with a cocoon covered with soil grains. Male and female imago (moth) exit the pupa by breaking the ventral portion of the thorax. The moth that comes out of the pupa is still very weak. A few hours later it can fly. On the head there is a coiled proboscis (trunk) and filiform antennae (like threads). The front leg is shorter than the hind leg. The female moth's abdomen is larger, but shorter than the male moth. The tip of the abdomen of the male moth is blunter and has more fine hair. The characteristics of the head color are orange, body color is cream to slightly yellow, wing color is brown with black spots, laying eggs under the leaves. The research location is at a position of ± 85 meters above sea level. Humidity 87%. Temperature 26 ° C. Laboratory room temperature 27 ° C. Screening temperature 27 ° C, green house temperature 30.4 ° C. The number of rainy days is 24 days. The duration of the sun's radiation is 53%. Rainfall 315 millimeters. Key words: morphology, size, shape, larva color, behavior of Crocidolomia pavonana